Reduce Graphene Decorated with Iron Oxide/ Polymer Composite for Photo-Fenton Pollutants Dye Degradation - Sara Abdul Karim Dawai (Journal of Global Pharma Technology, 2019)
The treatment processes for industrial wastewater contains organic pollutants and removal of heavy metal ions remain challenging. In this work,   photo Fenton reaction activity was used to degrade the organic pollutants by functional composite hydrogel. The hydrogel is made up of Fe3O4 particles, reduced graphene oxide (RGO) and polyacrylamide (PAM). It is prepared from rGO/Fe3O4 and by precipitation method, GO has been prepared from graphite by Hummers method. And exhibits the outstanding mechanical strength, Photo-Fenton activity by different decomposition data that were affected differently; pH, H2O2 concentration, dye concentration, temperature, irradiation time. The morphology of the composite and the average diameter was studied by Atomic Force Microscopy (AFM). The degradation of M.B dye by Fe3O4/rGO/PAM hydrogel composite was reached to 100% after 60 min under UV irradiation. Meanwhile, COD (Chemical Oxygen Demand) decreased to 21 mg/l after one hour's visible irradiation and became low (under range) after 2 hours. This study provides a new pathway to process the industrial wastewater of high consistence and difficult decomposition.Keywords: Photo- Fenton reaction, RGO/Fe3O4/PAM composite, Methylene Blue, COD.